2016
DOI: 10.3389/fnagi.2016.00283
|View full text |Cite
|
Sign up to set email alerts
|

Combining Exergame Training with Omega-3 Fatty Acid Supplementation: Protocol for a Randomized Controlled Study Assessing the Effect on Neuronal Structure/Function in the Elderly Brain

Abstract: A common problem in the older population is the risk of falling and related injury, immobility, and reduced survival. Age-related neuronal changes, e.g., decline in gray-and white-matter, affect neuronal, cognitive, and motor functioning. The improvement of these factors might decrease fall events in elderly. Studies showed that administration of video game-based physical exercise, a so-called exergame, or omega-3 fatty acid (FA) may improve motor and/or cognitive functioning through neuronal changes in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…The study was a randomized double-blinded, placebo-controlled trial involving older adults above 65 years. Detailed information about the study procedure and protocol has been previously described [ 53 ]. Between December 2015 and June 2016, potential participants were recruited from the Senior’s University Zurich (Switzerland), senior residency dwellings in Zurich (Switzerland), and through public advertisement and flyers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study was a randomized double-blinded, placebo-controlled trial involving older adults above 65 years. Detailed information about the study procedure and protocol has been previously described [ 53 ]. Between December 2015 and June 2016, potential participants were recruited from the Senior’s University Zurich (Switzerland), senior residency dwellings in Zurich (Switzerland), and through public advertisement and flyers.…”
Section: Methodsmentioning
confidence: 99%
“…stroke or epilepsy) that prevent training participation, (4) history of heart attack, (5) medication that interacts with NS (i.e., oral hypoglycemic drugs or anticoagulants), (6) medication that acts on neuronal level (i.e., psychotropic medications), (7) cognitive impairment (Mini Mental Status Examination < 22 points) [ 56 ], (8) signs of depression (Geriatric Depression Scale > 5 points), (9) electronic or metallic head implants (self-reported), and (10) personal history of dizziness (self-reported). Prior power calculation can be found in the previously published study protocol [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for human researches, a pilot study reported that combined omega-3 fatty acids, aerobic exercise, and cognitive stimulation may prevent gray matter volume loss in frontal, parietal, and cingulate cortex in patients with mild cognitive impairment [ 274 ]. A randomized controlled trial by Schättin and de Bruin [ 275 ] is now investigating the effectiveness of exergame training (a kind of physical exercise based on video games) combined with omega-3 fatty acid supplementation in counteracting age-dependent neuronal changes in the brain. From a clinical point of view, the combined antidepressant effects of exercise and omega-3 fatty acids underpin the “Antidepressant-Lifestyle-Psychological-Social (ALPS) depression treatment model”, an evidence-based integrated mental health approach including pharmaceutical medicines as well as psychological therapies, complementary medicines, nutraceuticals, and physical activity [ 276 ].…”
Section: Additional Effects Of Exercise and Omega-3 Fatty Acids On Dementioning
confidence: 99%